Optical emissions associated with narrow bipolar events from thunderstorm clouds penetrating into the stratosphere - Feifan Liu (Nature Portfolio, 2021)
Strong thunderstorms can reach the lower stratosphere and produce cloud-top blue emissions, affecting the exchange of greenhouse gases between the troposphere and stratosphere. Here, the authors reveal the direct link of blue emissions with the radio signals of one sort of intra-cloud discharges called NBEs.